The Possibility of Impossibility: Reading The Watermelon Woman with Derrida and Adorno - Christopher Morris (CINEJ Cinema Journal)
Hermeneutic criticism of The Watermelon Woman has been unable to reconcile the film’s closing affirmation of identity and possibility with the narrative that precedes it and especially with the acknowledgement that Fae Richards is not real. An approach derived from the commonality Derrida saw between his work and Adorno’s can show how the film narrates the fiction of identity and the possibility of impossibility.